Effect of ozonation combined with heterogeneous catalysts and ultraviolet radiation on recycling of gas-station wastewater - Eman A. Emam (Egyptian Journal of Petroleum)
Ozonation is extensively applied in the treatment of drinking water and wastewater due to the powerful oxidation potential of ozone. Heterogeneous catalytic ozonation (HCO) of wastewater proceeds through hydroxyl radicals as the oxidation species. The effect of ozonation alone and combined with catalysts in the presence and absence of UV-radiation was investigated to reuse the biologically pretreated gas-station wastewater instead of fresh water. Two types of catalysts: titanium dioxide (TiO2) and activated carbon (AC) were studied. The concentration of catalyst, dark adsorption, reaction time and the improvement of biodegradability were studied. The combination of catalysts and ozonation reveals a significant improvement in the removal of contaminants present in wastewater by using the ozonation, adsorption or photocatalysis systems. Maximum dissolved organic carbon (DOC) removal of 91% was achieved by the combination of ozone, TiO2 and the UV-radiation system. But, an increase in biodegradability from 0.12 to 0.33 was realised with ozone and the TiO2 system. Furthermore, the biodegradability was increased with increasing catalyst concentration combined with ozone up to 1 g/L with TiO2 and 0.5 g/L with AC.